Gambaran Ketidakadilan terhadap Perempuan dalam Novel Al-Hub Fi Zamani Al-Nafthi Karya Nawal Sa’dawi (Sebuah Kajian Feminisme) - Julian, Hendri; Jannah, Raudhatul; Yusliza, Yusliza; Burlianda, Muhammad (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the problems seen from a feminist perspective, in the form of forms of injustice against women contained in the novel